Phosphodiesterase Type IV Inhibitors Prevent Ischemia-Reperfusion-Induced Gastric Injury in Rats - Takashi Kyoi; Satoru Kitazawa; Koyuki Tajima; Xin Zhang; Yojiro Ukai (Elsevier, 2004)
The effects of selective inhibitors of phosphodiesterase type IV (PDE4) on ischemia-reperfusion-induced gastric injuries were investigated in rats. Gastric ischemia was induced by applying a small clamp to the celiac artery, and reoxygenation was performed by removal of the clamp. Ischemia-reperfusion produced gastric hemorrhagic injuries and increased the content of the proinflammatory cytokine tumor necrosis factor-α (TNF-α) and myeloperoxidase (MPO) activity in gastric mucosa. Rolipram (0.03 - 0.3 mg/kg, s.c.) and Ro-20-1724 (0.3-3mg/kg, s.c.) prevented the development of gastric injury in a dose-dependent manner, and it also inhibited the increase in mucosal TNF-α content and MPO activity induced by ischemia-reperfusion. The anti-ulcer drug irsogladine (1 - 10 mg/kg, p.o.), which is known to possess a PDE4 inhibitory action, also inhibited the gastric injury produced by ischemia-reperfusion, as well as the increase in TNF-α levels and MPO activity. It is concluded that the ability of PDE4 inhibitors to inhibit cytokine TNF-α synthesis and the infiltration of polymorphonuclear leukocytes underlies their gastroprotective effects in ischemia-reperfusion-induced gastric injury. Our experiments suggest that drugs that inhibit PDE4 isoenzyme, such as the anti-ulcer drug irsogladine, may be a useful adjunct therapy for the treatment of the gastric damage that follows ischemia-reperfusion. Keywords:: ischemia-reperfusion, gastric injury, phosphodiesterase type IV inhibitor, rolipram, irsogladine